A Review on Ultrasonic Neuromodulation of the Peripheral Nervous System: Enhanced or Suppressed Activities? - Bin Feng; Longtu Chen; Sheikh J. Ilham (Applied Sciences, 2019)
Ultrasonic (US) neuromodulation has emerged as a promising therapeutic means by delivering focused energy deep into the nervous tissue. Low-intensity ultrasound (US) directly activates and/or inhibits neurons in the central nervous system (CNS). US neuromodulation of the peripheral nervous system (PNS) is less developed and rarely used clinically. The literature on the neuromodulatory effects of US on the PNS is controversial, with some studies documenting enhanced neural activities, some showing suppressed activities, and others reporting mixed effects. US, with different ranges of intensity and strength, is likely to generate distinct physical effects in the stimulated neuronal tissues, which underlies different experimental outcomes in the literature. In this review, we summarize all the major reports that document the effects of US on peripheral nerve endings, axons, and/or somata in the dorsal root ganglion. In particular, we thoroughly discuss the potential impacts of the following key parameters on the study outcomes of PNS neuromodulation by US: frequency, pulse repetition frequency, duty cycle, intensity, metrics for peripheral neural activities, and type of biological preparations used in the studies. Potential mechanisms of peripheral US neuromodulation are summarized to provide a plausible interpretation of the seemly contradictory effects of enhanced and suppressed neural activities of US neuromodulation.